Risk management in digitalized educational environments: Teachers’ information security awareness levels - Sapanca, Hamza Fatih; Kanbul, Sezer (Frontiers in Psychology, 2022)
With the spread of Information and Communication Technologies (ICT) tools and the Internet, 21st-century technologies have significantly affected human life, and it has been desired to be obtained continuously. It has become challenging to protect information due to the increase in the methods by which malicious people can get information. As a result, it is crucial to determine people's awareness levels by revealing the risks and threats to information security. In this context, a study was conducted to show the awareness levels of teachers who come after the family in raising conscious individuals in society. For this purpose, a quantitative research method was adopted for the problem and sub-problems that form the basis of the research. The survey model, one of the research designs used within the framework of the quantitative research method, was used. Information Security Awareness Scale was applied to 394 teachers, and according to the results obtained, it was determined that the information security awareness level of the teachers was moderate. According to the attacks and threats sub-dimension, which includes technical issues, it has been determined that the awareness levels of the teachers are at a medium level. The study results show that female teachers' information security awareness levels are lower than male teachers. In comparison, the awareness levels of those who received information security awareness training and information technology teachers are higher.